Improving Teachers Knowledge in Making Visual Support for Children with Autism Spectrum Disorders - Rifa Hidayah; Novia Solichah (Psympathic : Jurnal Ilmiah Psikologi, 2022)
This study is motivated by the limited knowledge of teachers in creating visual support programs for children with autism spectrum disorders (ASD). It is essential for teachers to increase their knowledge base in creating programs specifically designed for ASD children. Therefore, this study aims to empirically examine the effect of a visual support program to increase the knowledge of teachers in creating visual support programs for ASD children using a pre-experiment with one group pretest-post test design. The participants are nine teachers of ASD children, and non-parametric statistical analysis is conducted to test the difference in knowledge scores before and after administering the program. The results show that the visual support programs effectively increases the knowledge of teachers in making visual support with sig. .01 and effect size of 72%.